Monitoring the Microcirculation in Critical Conditions: Possibilities and Limitations - T. O. Tokmakova; S. Yu. Permyakova; A. V. Kiseleva; D. L. Shukevich; E. V. Grigoryev (Общая реаниматология)
The paper provides an analytical review of the references on the role of microcirculatory disorders in the development of critical conditions, the significance of circulatory monitoring, specifically, to make a presumptive prognosis of multiple organ dysfunction. It defines main directions in the diagnosis and correction of microcirculatory disorders as direct (infusion therapy) and indirect (influence on the components of a systemic inflammatory response, by extending to microcirculatory correction) microcirculatory exposures. Key words: critical conditions, multiple organ dysfunction, procedures to evaluate and correct microcirculation.